Ein temperaturstabilisierungssystem auf der basis genetischer algorithmen für die vliesstoffherstellung - Khalimovskyy, O.; Pryymak, B. (NTU "KhPI", 2010)
A genetic algorithm based temperature stabilization system at the production of unwoven material from a polypropylene is proposed. Results of modelling confirm high performance of control system and robustness against variations of non-stationary parameters of plant.
A genetic algorithm based temperature stabilization system at the production of unwoven materials